Formulation and Implementation of the Independent Curriculum Policy at the Primary and Secondary Education Levels: A Case Study at SDN 1 and SMPN 2 Jerowaru - Sopiandi, Muhammad Syukur (MANAZHIM, 2026)
This study addresses the limited research on the formulation and implementation of the Independent Curriculum in rural primary and secondary schools, despite its critical influence on teaching quality and student learning outcomes. The research aims to (1) analyze the curriculum policy formulation process at SDN 1 Jerowaru and SMPN 2 Jerowaru, (2) describe its implementation in both schools, and (3) evaluate its impact on the quality of teaching and learning. Employing a qualitative case study design, data were collected from 34 purposively selected participants—including principals, curriculum coordinators, teachers, students, parents, and education supervisors—through semi-structured interviews, non-participant observations, and document analysis. Thematic analysis, supported by NVivo software, revealed that the formulation process was collaborative and contextually responsive, with school leaders and teachers demonstrating strong conceptual understanding but expressing a need for greater operational clarity. Implementation strategies varied by context: SDN 1 adopted project-based, student-centered learning integrating local environmental and cultural themes, while SMPN 2 emphasized subject-based instruction aligned with national standards. The Independent Curriculum was found to enhance teaching quality by fostering teacher autonomy, creativity, and reflective practice, while students exhibited improved critical thinking, collaboration, and communication skills. The study concludes that successful curriculum reform in rural contexts depends on the alignment of policy design, leadership, teacher competence, and local adaptability. It contributes theoretical insights into decentralized curriculum implementation and offers practical recommendations for professional development, mentoring, and resource distribution. Future research is recommended to explore the sustainability of such reforms, digital integration, and implementation in resource-constrained environments.